Pengaruh Aktivitas Pedagang Kaki Lima terhadap Tingkat Pelayanan Jalan di Jalan Cikutra, Kota Bandung - Achmad Fauzan Iscahyono; Thasya Putri Aurora; Renny Desiana (Universitas Dr. Soetomo, 2023)
Street vendors around Cikutra Street are growing rapidly because of their location close to centers of community activity, such as residential locations, as well as education and health facilities. It causes the condition of the road network and facilities for pedestrians to not function properly. This study objectives to determine the impact of street vendor activity on the level of service on Cikutra Street, Bandung City. This research is a kind of quantitative studies in which the evaluation of level of road service uses the 2014 Indonesian Highway Capacity Guidelines. Based at the results of the analysis, the existence of street vendor activity along Cikutra Street has an influence on the level of road service. The existence of these street vendor activities has an impact on decreasing the level of service on Cikutra Street. This happens because it tends to be caused by travel delays, the physical condition of the street, the geometry of the street, and the volume of vehicle traffic flow on that street section. Even if the street vendors are abolished or relocated to other locations, the volume of vehicles will still be high because there are other commercial activities that are located on the edge of Cikutra Street and can affect the composition of vehicles passing through Cikutra Street.